Music for Mohini: A Critical Analysis of Novel of Bhabani Bhattacharya: Exploring Class Struggles and Marriage in Bhabani Bhattacharya's Novel (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bhabani Bhattacharya, an Indian writer, has overwhelmingly expounded on class battles, which are across the board in the Indian culture because of the standing framework and colonization. His tale A tranquil, unassuming novel of melodious appeal and irresistible funninessThe story couldn't be easier. A young lady weds and in course of time delivers a youngster. The young lady is city reproduced — her significant other, a Sanskrit researcher, who has his heart in a remote town and where he takes her after marriage. There's nothing more to it.Youthful, fun loving and insidious Mohini dreams of a spouse however her training and childhood and the thoughts of liberal teacher father are unsuitable to her Brahmin traditioned grandma. Marriage for affection is disposed of, marital promotions in the papers bring just humiliation, and it is through a crystal gazer that a match is made.